2017
DOI: 10.1371/journal.pone.0187422
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome DNA methylation characteristics in pediatric precursor B cell acute lymphoblastic leukemia (BCP ALL)

Abstract: In addition to genetic alterations, epigenetic abnormalities have been shown to underlie the pathogenesis of acute lymphoblastic leukemia (ALL)—the most common pediatric cancer. The purpose of this study was to characterize the whole genome DNA methylation profile in children with precursor B-cell ALL (BCP ALL) and to compare this profile with methylation observed in normal bone marrow samples. Additional efforts were made to correlate the observed methylation patterns with selected clinical features. We asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…In our previous study [ 5 ] material comprised 38 samples of BM obtained from patients with pediatric precursor-B acute lymphoblastic leukaemia, at the time of the final ALL diagnosis, and 4 control non-leukemic samples. The analysis of cytogenetic ALL subtypes revealed that among BCP ALL SC patients there were 2 cases of triploidy and 12 cases of hyperploidy which might serve as a control for the analyzed BCP ALL PP patients.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous study [ 5 ] material comprised 38 samples of BM obtained from patients with pediatric precursor-B acute lymphoblastic leukaemia, at the time of the final ALL diagnosis, and 4 control non-leukemic samples. The analysis of cytogenetic ALL subtypes revealed that among BCP ALL SC patients there were 2 cases of triploidy and 12 cases of hyperploidy which might serve as a control for the analyzed BCP ALL PP patients.…”
Section: Methodsmentioning
confidence: 99%
“…The previous results also showed, that factors such as gender and age are not important confounders for the global methylation profile differentiation of pediatric leukaemia. [ 5 ] DNA was purified using QIAamp DNA Blood Mini Kit (QIAGEN), assessed for fragmentation by agarose gel electrophoresis and quantified using Qubit 2.0 fluorimeter (Thermo Fisher Scientific). CpG methylation analysis was performed using Illumina (San Diego, CA) MethylationEPIC BeadChip, allowing analysis of 850K sites per sample.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides aberrant genetic modifications, epigenetic irregularities have been shown to trigger the pathogenesis of childhood ALL (Taylor et al, 2007; Chaber et al, 2017). It has been described that aberrant methylation is associated with prognosis (Wong et al, 2000), cytogenetic subtype (Zheng et al, 2004), prediction of treatment outcome (Milani et al, 2010) and relapse (Matsushita et al, 2004; Hogan et al, 2011) in childhood acute leukemias.…”
Section: Childhood Acute Lymphoblastic Leukaemia (All)mentioning
confidence: 99%